Obesity Is Significantly Associated With Cardiovascular Disease Risk Factors in 2‐ to 9‐Year‐Olds. Issue 12 (13th October 2014) - Messiah, Sarah E.; Vidot, Denise C.; Gurnurkar, Shilpa; Alhezayen, Reem; Natale, Ruby A.; Arheart, Kristopher L.
<x xml:space="preserve">Abstract</x> The objective of this analysis was to estimate the prevalence of cardiovascular disease risk factors in ethnically diverse young children. A retrospective medical chart review identified overweight/obese 2‐ to 9‐year‐old children (N=147) from a local pediatric clinic who were matched (for age, sex, and ethnicity) with normal weight patients from the 2005–2010 National Health and Nutrition Examination Survey (N=294). Comparisons of mean systolic blood pressure and diastolic blood pressure, total, and high‐density lipoprotein (HDL) cholesterol were conducted. Results showed that compared with the population‐based normal‐weight sample, the local overweight/obese sample was significantly more likely to have diastolic prehypertension (15% vs 75%, P<.0001), systolic prehypertension (10% vs 43%, P<.0001), and the lowest quintile of HDL cholesterol (19% vs 34%, P=.003). At this young age, excess weight is significantly associated with cardiovascular disease risk factors. These results suggest that overweight/obese children in this age group should be monitored closely to prevent potential chronic disease risk.